PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. SRIMASARI ARTA PRIMA DENPASAR - Ni Luh Putu Meli Ariyanti; Dewiwati Sujadi (Journal Research of Management, 2023)
at employee performance is positively and significantly influenced by partial motivation, with tcount = 3.612 > ttable value = 2.026, rejecting Ho and accepting H1. With tcount = 3.473 > ttable value = 2.026, the workplace has a positive and substantial impact on employee performance, rejecting hypothesis Ho and accepting hypothesis H2. Employee performance is more strongly influenced by the motivation variable, which has a standardized beta coefficient () of 0.265, than by the employee work environment variable. 67.2% of the total was determined, while the remaining 0.328, or 32.8%, was explained by factors or other causes not included in the research model. Researchers' recommendations for improving employee performance at PT. Srimasari Arta Prima Denpasar include increasing work motivation by offering suitable incentives, creating a comfortable work atmosphere among coworkers, and maintaining job quality.